Consumer perception versus scientific evidence of farmed and wild fish: insights from Malaysia - Goh, Ee Von; Azam-Ali, Susan; Mitra, Soma Roy; McCullough, Fiona (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2023)
Understanding consumer perceptions is crucial for shaping market demand, building consumer confidence, and promoting sustainable practices in the aquaculture sector. The main goal of this study is to examine consumers' perceptions of farmed and wild fish on various attributes, aiming to identify any discrepancies between consumer perception and scientific facts. Using random purposive sampling, a survey was conducted with 250 consumers in selected Malaysian populations recruited via street-intercept interviews. The findings reveal that the debate between consuming farmed fish and wild fish lacks a clear answer, with consumer perceptions, especially regarding freshness and sensory characteristics, often differing from scientific evidence. While fish farming offers advantages in quality control and post-mortem biochemistry, the nutritional composition of fish can vary based on farming conditions. To ensure the success of the aquaculture industry in Malaysia, there is a need to enhance practices, raise awareness among aquaculturists, and educate consumers about the benefits of well-managed aquaculture. By adopting a multidisciplinary approach and addressing the crucial nexus between consumer perceptions and sustainable aquaculture, this study makes a valuable and timely contribution to the ongoing discourse in the aquaculture sector. It offers insights that can inform strategies for promoting responsible seafood consumption and advancing the sustainability agenda in Malaysia's aquaculture industry.